Microglial activation and neurobiological alterations in experimental autoimmune prostatitis-induced depressive-like behavior in mice - Du HX (Dove Medical Press, 2019)
He-Xi Du,1–3 Xian-Guo Chen,1–3 Li Zhang,1–3 Yi Liu,1–3 Chang-Sheng Zhan,1–3 Jing Chen,1–3 Yong Zhang,1–3 Zi-Qiang Yu,1–3 Jin Zhang,4,5 Hong-Yi Yang,4,5 Kai Zhong,4,5 Chao-Zhao Liang1–31Department of Urology, The First Affiliated Hospital of Anhui Medical University, Anhui Medical University, Hefei 230022, People’s Republic of China; 2Institute of Urology, Anhui Medical University, Hefei 230022, People’s Republic of China; 3Anhui Province Key Laboratory of Genitourinary Diseases, Anhui Medical University, Hefei 230022, People’s Republic of China; 4High Magnetic Field Laboratory, Hefei Institutes of Physical Science, Chinese Academy of Sciences, Hefei 230031, People’s Republic of China; 5Key Laboratory of Anhui Province for High Magnetic Resonance Imaging, Hefei 230031, People’s Republic of ChinaBackground: Patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) frequently show depressive symptoms clinically and increasing evidence indicates a correlation between CP/CPPS and depression. However, the underlying mechanisms of CP/CPPS-related depression remain poorly understood. Here, we sought to determine the role of hippocampal microglial activation and neurobiological changes in a mouse model of experimental autoimmune prostatitis (EAP)-induced depression and the treatment efficacy of Chinese herb extract baicalein.Methods: EAP was induced through intradermal injection of prostate antigen and adjuvant twice. Then, mice were assessed for affective behaviors in the open field test, elevated plus maze, forced swim test, and tail suspension test. The morphology and function of microglia and astrocytes were detected by immunofluorescence, Western blotting, and transmission electron microscopy. Proinflammatory mediators along with serotonin transporter (SLC6A4/SERT) and indoleamine 2,3-dioxygenase (IDO) were quantified with reverse transcription-polymerase chain reaction (RT‑PCR), and serum serotonin concentrations were measured by enzyme-linked immunosorbent assay (ELISA). Proton magnetic resonance spectroscopy (1H-MRS) was performed to measure hippocampal glutamate levels. In addition, baicalein was used in a subset of EAP mice to test its anti-depressant action.Results: EAP was successfully established and induced depressive- and anxiety-like behavior in mice. Increasing levels of co-expressed ionized calcium-binding adapter molecule 1 (Iba1) and glial fibrillary acidic protein (GFAP) and ultrastructural observations suggested microglial activation and reactive astrocytosis in the hippocampus. These activated microglia resulted in increased expressions of multiple proinflammatory cytokines. Simultaneously, EAP mice showed higher gene expressions of SLC6A4 and IDO and lower concentrations of serotonin. 1H-MRS indicated a decrease in the glutamate + glutamine (Glx)/total creatine (tCr) ratio in EAP mice. Furthermore, baicalein treatment alleviated the depressive-like behavior and neuroinflammation by suppressing the nuclear factor-kappa B (NF-κB) pathway.Conclusion: Our data indicate that EAP-induced depressive-like behavior is linked to microglia activation and subsequent neurotransmitter metabolism. Moreover, baicalein attenuates behavioral changes by inhibiting neuroinflammation via downregulation of the NF-κB pathway.Keywords: EAP, microglial activation, serotonin, neurochemical changes, baicalein